Broadband and e - Government Services in South East Europe: Comparative Analysis, Impact and Policy Recommendations - Konstantinos Antonis; Christos Bouras; Fabrizio D’Elia; Annalisa Di Vincenzo; Georgios Diles; Vasileios Kokkinos; Andreas Koskeris (International Journal of Interdisciplinary Telecommunications and Networking, IGI Global, 2015)
The European Commission acknowledging the significance of broadband for the improvement of citizen welfare and its economic benefits, has put in place targets for the diffusion of broadband to all citizens and businesses in the European Union. This manuscript comparatively assesses the current state of affairs in broadband and digital public services in selected South East Europe (SEE) countries in order to identify weaknesses and highlight strengths, and attempts to measure the impact and effectiveness of broadband on the economy. To this direction, the authors focus on evaluating the correlation between broadband and growth and employment. They also estimate the savings achieved by the usage of e-services and the potential savings that will follow their increased utilization over the next years. The analysis is followed by a number of recommendations that aim to support informed decision making. The manuscript builds on four surveys that took place during the second quarter of 2013.